Temporal Network of Depressive Symptoms across College Students with Distinct Depressive Trajectories during the COVID-19 Pandemic - Ma, Zijuan; Zhao, Jingbo; Chen, Huilin; Tao, Yanqiang; Zhang, Yifan; Fan, Fang (Depression and Anxiety, 2023)
Background. There are marked differences in how individuals respond and adapt to depressive symptoms over time during the strain of public health emergencies; however, few studies have examined the interrelations between depressive symptoms in distinct depressive trajectories from the COVID-19 outbreak period to the COVID-19 control period. Therefore, this study conducted cross-lagged panel networks to investigate the temporal relationships between depressive symptoms across distinct depressive trajectories from the COVID-19 outbreak period (T1) to the COVID-19 control period (T2). Methods. A total of 35,516 young participants from the College Students’ Behavior and Health Cohort during the COVID-19 pandemic were included in the current study. Depressive symptoms were self-reported using the nine-item Patient Health Questionnaire. Unique longitudinal relationships between symptoms during the COVID-19 pandemic were estimated using a cross-lagged panel network. Results. Longitudinal relationships across distinct depressive trajectories were unique during the COVID-19 pandemic. Specifically, suicidal ideation at T1 in the chronic- and delayed-dysfunction groups was most predictive of other symptoms at T2, whereas “sleep” at T1 in the recovery group and “lack of energy” at T1 in the resistance group may be strongly related to the remission of other depressive symptoms at T2. Conclusions. These exploratory findings demonstrate the directionality of relationships underlying individual symptoms in the youth and highlight suicidal ideation, sleep, and energy as potential influencers of other depressive symptoms across distinct depressive trajectories. Targeting those symptoms during the outbreak period of COVID 19 would theoretically have been beneficial in preventing and/or reducing the likelihood of spontaneous depression during the subsequent control period.